The Influence of Service Quality on Consumer Loyalty with the Mediation of Customer Satisfaction on Dahirang Kapuas Antique Souvenirs - Aryawan Aryawan; Usup Riassy Christa; Meitiana Meitiana; Vivy Kristinae (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
This study aims to analyze the effect of service quality on consumer loyalty through customer satisfaction at Antique Souvenirs in Dahirang, Kapuas, Central Kalimantan. This topic is important because local souvenir retail businesses need to maintain competitiveness through reliable, responsive, informative, and customer-oriented service experiences. The study used a quantitative explanatory approach involving 100 consumers selected through purposive sampling. Data were collected using a structured questionnaire and analyzed using Smart Partial Least Squares. The results showed that service quality has a positive and significant effect on customer satisfaction and consumer loyalty. Customer satisfaction also has a positive and significant effect on consumer loyalty and partially mediates the relationship between service quality and loyalty. These findings confirm that loyalty is not only shaped by product uniqueness, but also by services that create trust, value, and satisfaction.